Direct numerical simulation of the Taylor–Couette flow with the asymmetric end-wall boundary conditions - Tuliszka-Sznitko, E.; Kiełczewski, K. (Archives of Mechanics, 2016)
In the paper the authors present the results obtained during a direct numerical simulation of the transitional Taylor–Couette flow in closed cavity. The spectral vanishing viscosity method is used to stabilize computations for higher Reynolds numbers. The Taylor–Couette flow is widely used for studying the primary pattern formation, transitional flows and fully turbulent flows. The Taylor–Couette flow is also important from engineering point of view: the results can be interesting for engineers dealing with gas turbines and axial compressors. In the paper the attention is focused on the influence of the end-wall boundary conditions on the flow structures and on statistics (i.e. the radial profiles of the angular velocity, angular momentum, torque, the Reynolds stress tensor components). The results are discussed in the light of experimental and numerical data published in literature (F. Wendt, Ing.-Arch., 4, 1933; H. Brauckmann, B. Eckhardt, J. Fluid Mech., 718, 2013).